Prognostic Impact of Acute Myocardial Infarction in Patients Presenting With Ventricular Tachyarrhythmias and Aborted Cardiac Arrest. Issue 19 (2nd October 2018) - Behnes, Michael; Mashayekhi, Kambis; Weiß, Christel; Nienaber, Christoph; Lang, Siegfried; Reiser, Linda; Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Schupp, Tobias; et al.
Abstract : Background: The study sought to assess the prognostic impact of acute myocardial infarction (AMI) with and without ST‐segment–elevation myocardial infarction (STEMI and NSTEMI) in patients with ventricular tachyarrhythmias and sudden cardiac arrest (SCA) on admission. Methods and Results: A large retrospective registry was used including all consecutive patients presenting with ventricular tachycardia (VT), fibrillation (VF), and sudden cardiac arrest (SCA) on admission from 2002 to 2016. AMI versus non‐AMI and STEMI versus NSTEMI were compared applying multivariable Cox regression models and propensity‐score matching for evaluation of the primary prognostic end point defined as long‐term all‐cause mortality at 2.5 years. Secondary end points were 30 days all‐cause mortality, cardiac death at 24 hours, in hospital death, and recurrent percutaneous coronary intervention (re‐PCI) at 2.5 years. In 2813 unmatched high‐risk patients with ventricular tachyarrhythmias and SCA, AMI was present in 29% (10% STEMI, 19% NSTEMI) with higher rates of VF (54% versus 31%) and SCA (35% versus 26%), whereas VT rates were higher in non‐AMI (56% versus 30%) ( P  < 0.05). AMI‐related VT ≥48 hours was associated with higher mortality (log rank P  = 0.001). Multivariable Cox regression models revealed non‐AMI (hazard ratio = 1.458; P  = 0.001) and NSTEMI (hazard ratio = 1.460; P  = 0.036) associated with increasing long‐term all‐cause mortality at 2.5 years, which was also proven after propensity‐score matching (non‐AMI versus AMI: 55% versus 43%, log rank P  = 0.001, hazard ratio = 1.349; NSTEMI versus STEMI: 45% versus 34%, log rank P  = 0.047, hazard ratio = 1.372). Secondary end points including 30 days and in‐hospital mortality, as well as re‐PCI were higher in non‐AMI patients. Conclusions: In high‐risk patients presenting with ventricular tachyarrhythmias and SCA, non‐AMI revealed higher mortality than AMI, respectively NSTEMI than STEMI, alongside AMI‐related VT ≥48 hours.